Green building assessment tools: evaluating different tools for green roof system - Fauzi, Muhammad Ashraf; Abdul Malek, Nurhayati (Contemporary Research Center Australia, 2013)

(untitled)
Intense progress, technological competition and globalization had incurred dramatic changes in building technology. The issues of building sustainability’s have been a major subject of debates and arguments among the practitioners. The emergence of green building assessment tools have somehow given the guidelines and foundation for a building to be certified as a sustainable building or in the new term would be called as green building. One important component in green building is the green roof system. How far the existing assessment tools evaluating and credit to the green roof system will be analyzed in this study. The establish assessment tools such as Building Research Establishment Environment Assessment Method (BREEAM), Leadership in Energy and Environmental Design (LEED), CASBEE, BCA Green Mark and Malaysian very own Green Building Index (GBI) will be compared among each other to determine which tools give higher marks for green roof technology. The result of this study will enables to determine in which assessment tool that gives most priority and benefits to developers when implementing green roof system.